2017
DOI: 10.21037/jtd.2017.02.90
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lymph node management on resectable non-small cell lung cancer patients

Abstract: Results: The average number of dissected LNs was 22.7±12.8. Tumor recurrence was found in 51.3% and overall mortality was 43.3%. The number of dissected LNs was a prognostic factor for tumor recurrence [HR 0.98, 95% confidence interval (CI): 0.96-0.99]. There was a significant difference at the cut-pointed value of 11 dissected LNs for tumor recurrence (HR 2.22, 95% CI: 1.26-3.92). Dissection less than 11 nodes and less than 5 stations indicated a poor prognostic factor for tumor recurrence: for 3-4 stations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…1 In 2014, the CoC endorsed a removal of at least 10 regional LNs for early-stage NSCLC. 7 Meanwhile, a number of studies also proposed the optimal numbers for LN evaluation, with the suggestions ranging from four to 20, based on the analyses of survival advantage and/or nodal upstaging (Table 3 2,[8][9][10][16][17][18][19][20][21][22][23][24][25][26] ). Previous studies indicated that the possibility of LN metastasis increases with greater tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…1 In 2014, the CoC endorsed a removal of at least 10 regional LNs for early-stage NSCLC. 7 Meanwhile, a number of studies also proposed the optimal numbers for LN evaluation, with the suggestions ranging from four to 20, based on the analyses of survival advantage and/or nodal upstaging (Table 3 2,[8][9][10][16][17][18][19][20][21][22][23][24][25][26] ). Previous studies indicated that the possibility of LN metastasis increases with greater tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…As compared with techniques used in previous studies, the present ALT technique enables en bloc dissection of three times as many lymph nodes, which increased the nodal upstaging rate (Table 5) (10,(12)(13)(14). Dissection of fewer than 11 lymph nodes is associated with a poor prognosis (15); thus, extended mediastinal LND might improve outcomes for left NSCLC with micrometastases. However, adapting LND via ALT is not practical for all patients with left NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended number of nodes or stations for accurate nodal staging varies among sources. Some authors have proposed that 11-14 lymph nodes or at least 5 stations be resected [25,26]. The guidelines of the European Society of Thoracic Surgeons recommend systematic MLND for all resectable lung cancer, including at least 3 N2 stations [5].…”
Section: Kjtcvsmentioning
confidence: 99%
“…Many researchers have explored risk factors for nodal upstaging, including those pertaining to patients (such as diabetes mellitus, history of tuberculosis, and connective tissue disorders) and to tumor-related factors (such as central location, higher T stage, higher standardized uptake value, and histotype) [23,26]. We did so as well and found that only tumor-related factors (namely serum CEA levels, lesion size, and tissue-confirmed pleural invasion) heightened the risk of nodal upstaging.…”
Section: Kjtcvsmentioning
confidence: 99%